Regulation of Escherichia coli Group 2 Capsule Gene Expression: A Mini Review and Update - Aldawood, Esraa; Roberts, Ian S. (Frontiers in Microbiology, 2022)
The expression of a group 2 capsule (K antigen) such as the K1 or K5 antigen, is a key virulence factor of Escherichia coli responsible for extra-intestinal infections. Capsule expression confers resistance to innate host defenses and plays a critical role in invasive disease. Capsule expression is temperature dependent being expressed at 37°C but not at 20°C when outside the host. Group 2 capsule gene expression involves two convergent promoters PR1 and PR3, the regulation of which is critical to capsule expression. Temperature-dependent expression is controlled at transcriptional level directly by the binding of H-NS to PR1 and PR3 and indirectly through BipA with additional input from IHF and SlyA. More recently other regulatory proteins, FNR, Fur, IHF, MprA and LrhA have been implicated in regulating capsule gene expression in response to other environmental stimuli and there is merging data for the growth phase dependent regulation of the PR1 and PR3 promoters. The aim of the present Mini Review is to provide a unified update on the latest data on how the expression of group 2 capsules is regulated in response to a number of stimuli and the growth phase something that has not to date been addressed.